Some aspects of methodology division of land categorized by main purpose - Lobunko, A. (Land Management, Cadastre and Land Monitoring, 2017)
Proved that the methodology of the existing division of land by class as the main pur‐ pose formed in Ukraine according to the economic, social and environmental interests of society and citizens of different period of development. However, it needs to be improved, taking into account the provisions of land classification nomenclature CORINE Programme of the European Union.